Literature Review: Konsep Religiusitas Dan Spiritualitas Dalam Penelitian Psikologi di Indonesia - Muhammad Anjar Gagahriyanto (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study, using the narrative literature review method, was conducted to rediscuss the concepts of religiosity and spirituality in Indonesia, specifically in psychological research. Based on 10 articles that had been investigated, it is known that religiosity in Indonesian psychological research has been explained consistently. In short, religiosity is understood as the feelings and experiences that a person has towards their religion, how far a person believes in the said religion, and how obedience a person is when it comes to the rules and rituals that need to be done. Meanwhile, spirituality tends to have several meanings that may or may not involve religions. Generally, spirituality can be understood as a way of being, perception, and awareness that a person has towards the transcendence or beyond their existence that become the driving force to search for the meaning and understanding of life. The transcendence or the beyond human aspect in spirituality concept can be seen as one of the reasons why spirituality overlaps with religiosity. The difference between them is that spirituality tends to be universal and not limited to specific religion or belief system, thus making it more abstract, subjective, and personal compared to religiosity. Despite having overlaps, religiosity and spirituality can be distinguished from one another and have their own roles for individuals.Â